Noninvasive measure of treatment response in non‐alcoholic steatohepatitis: Insights from EMMINENCE and meta‐analysis. Issue 7 (1st June 2021) - Davison, Beth A; Edwards, Christopher; Loomba, Rohit; Harrison, Stephen A; Cotter, Gad; Alkhouri, Naim; Koch, Gary G; Dittrich, Howard C
Abstract: Background and Aim: Liver histology changes are the current gold standard for evaluating non‐alcoholic steatohepatitis (NASH), but are limited by their invasiveness and variability for sampling and interpretation. We evaluated noninvasive biomarkers as an indication of histologic changes in NASH. Methods: Associations between 12‐month biomarker and NASH Clinical Research Network histologic score changes in 339 patients with NASH in the EMMINENCE trial was examined with multivariable models and partial canonical correlation. A meta‐analysis of 17 NASH trials including 3717 patients examined associations between these same changes and histologic response within treatment groups, and treatment effects on biomarkers and on liver histology. Biopsy measures assessed were changes in ballooning, steatosis, inflammation, and fibrosis, NASH improvement without worsening of fibrosis, and fibrosis improvement without worsening of NASH. All analytic methods suggest that a combination of aspartate aminotransferase (AST), cytokeratin‐18 (CK‐18 [M30 or M65]), and hemoglobin A1C (HbA1c) changes best predicts overall liver biopsy changes in response to interventions. Results: The weighted average of standardized mean changes (0.403 × AST, 0.314 × CK‐18, 0.283 × HbA1c) facilitated comparisons of within‐group responses and treatment effects among studies included in the meta‐analysis. This composite in EMMINENCE discriminated between patients with and without NASH resolution without worsening fibrosis with area under the receiver‐operator characteristic curve of 0.7880, and for fibrosis improvement without NASH worsening of 0.7553. Conclusion: A composite score based on changes in AST, HbA1c, and CK‐18 could serve as a surrogate for liver histologic improvement and an effective objective, noninvasive tool for comparative assessment of treatment effects of novel interventions. Abstract : Liver histology changes are the current gold standard for evaluating treatments for non‐alcoholic steatohepatitis (NASH), but are limited by their invasiveness and variability for sampling and interpretation. We evaluated noninvasive biomarkers as an indication of histologic changes in NASH. A composite score based on changes in AST, HbA1c, and CK‐18 could serve as a surrogate for liver histologic improvement and an effective objective, noninvasive tool for comparative assessment of treatment effects of novel interventions.